2019
DOI: 10.1080/15592294.2019.1629232
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polybrominated biphenyl and stochastic epigenetic mutations: application of a novel epigenetic approach to environmental exposure in the Michigan polybrominated biphenyl registry

Abstract: Endocrine-disrupting compounds are associated with altered epigenetic regulation and adverse health outcomes, although inconsistent results suggest that people have varied responses to the same exposure. Interpersonal variation in response to environmental exposures is not identified using standard, population-based methods. However, methods that capture an individual's response, such as analyzing stochastic epigenetic mutations (SEMs), may capture currently missed effects of environmental exposure. To test wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 81 publications
7
17
0
Order By: Relevance
“…DNA methylation outlier burden measures were strongly associated with cell proportions and other technical factors, again, confirming previous findings [13,14]. Moreover, in this study, batch effects were confounded by wave of data collection in the LBC1921 and LBC1936.…”
Section: Dna Methylation Outlier Burden and Agesupporting
confidence: 90%
See 4 more Smart Citations
“…DNA methylation outlier burden measures were strongly associated with cell proportions and other technical factors, again, confirming previous findings [13,14]. Moreover, in this study, batch effects were confounded by wave of data collection in the LBC1921 and LBC1936.…”
Section: Dna Methylation Outlier Burden and Agesupporting
confidence: 90%
“…DNA methylation outlier burden was highly positively skewed and consequently a log 10 -transformed version of outlier burden used in all analyses. This is consistent with previous findings [13,14]. When looking at outlier burden per CpG site rather than per individual, Wang and colleagues [13] reported that at 64% of CpG sites, at least one out of 385 individuals in SATSA had an outlier.…”
Section: Dna Methylation Outlier Burdensupporting
confidence: 89%
See 3 more Smart Citations